2012
DOI: 10.1590/s0036-36342012000400014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social networks on tobacco use among high-school adolescents in Mexico

Abstract: The effects of social networks on tobacco use among high-school adolescents in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Social smoking among adolescents provides opportunities for bonding and group membership that may transition from one time or space (e.g., day time in schools) to another (e.g., evening and nights during parties and clubbing) [ 47 ]. Even though most adolescents minimize the importance of peer influence over their smoking behavior, they readily describe social interchange networks, in which simultaneous cigarette smoking and sharing occurs [ 23 ]. These findings provide evidence for the operation of self-selection and peer-influence processes on adolescent smoking behaviors [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social smoking among adolescents provides opportunities for bonding and group membership that may transition from one time or space (e.g., day time in schools) to another (e.g., evening and nights during parties and clubbing) [ 47 ]. Even though most adolescents minimize the importance of peer influence over their smoking behavior, they readily describe social interchange networks, in which simultaneous cigarette smoking and sharing occurs [ 23 ]. These findings provide evidence for the operation of self-selection and peer-influence processes on adolescent smoking behaviors [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors that contribute to making adolescents living in Mexico a particularly vulnerable risk group for tobacco use include but may not be limited to easy access to cigarettes [ 22 ], peer pressure [ 23 ], social acceptability [ 24 ], parental use [ 24 , 25 ], aggressive tobacco industry marketing [ 21 , 26 ], and most importantly, the fact that even though smoking in enclosed public places (i.e., offices, schools, government buildings, and restaurants) is strictly prohibited, compliance is low [ 27 29 ]. Further exacerbating the problem is the reality that in Mexico, tobacco companies are allowed to sell “kiddie packs” and even “individual cigarettes” mainly by street vendors (many of them kids themselves) [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a friendship structure within a school or classroom can be diagramed as a sociometric network by mapping the friendships, in the form of lines, among students. 20 One method of fostering behavior changes through sociometric networks is using community opinion leaders (CPOLs). 21 In this approach influential individuals are identified and trained to be change agents.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies found in-degree centrality (popularity relating to the number of people who have nominated each individual as a friend) to be related to smoking (44,53,54), rated high, medium and low. One study broke this down by school type according to low and high smoking prevalence, and found that the school with a high smoking prevalence showed no difference, whereas in the school with a low smoking prevalence, popular students were less likely to be smokers (29).…”
Section: Network Positionmentioning
confidence: 99%
“…This study was rated low quality. Three studies related out-degree centrality (popularity relating to the number of people nominated as a friend by each individual) to smoking (37,53), with one showing it to have a protective effect (54). Whilst two studies found no association with smoking and outdegree centrality (30,44).…”
Section: Network Positionmentioning
confidence: 99%